2018
DOI: 10.1111/1348-0421.12637
|View full text |Cite
|
Sign up to set email alerts
|

Synovial GATA1 mediates rheumatoid arthritis progression via transcriptional activation of NOS2 signaling

Abstract: Transcriptional regulation of inducible nitric oxide synthase (iNOS) is critically involved in the pathogenesis and progression of rheumatoid arthritis (RA); however, the specific transcription factors that control this process remain largely unidentified. In the present study, it was discovered that expression of the key erythroid factor, globin transcription factor 1 (GATA1), is significantly greater in human RA synovial tissues than in osteoarthritis (OA) tissues. IL 6 was found to induce synovial GATA1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…As shown in Figure 4 , the HT extract significantly reduced the secretion of IL-6 and NO under the nontoxic dosages, which indicated that the HT formula would be a potential anti-inflammatory formula in accordance with the prediction results. Furthermore, our experimental results suggested that the HT extract could decrease the LPS-induced excessive expression of the iNOS ( Figure 5 ), which has been reported to promote the production of IL-6 and NO during the development of RA (Li et al, 2017; Liu et al, 2018). As well known, iNOS is the downstream signal in the network of inflammatory cascade reaction, and several signaling pathways including the Toll-like receptor signaling pathway (Li et al, 2019), PI3K–Akt signaling pathway (Cao et al, 2019), HIF-1 signaling pathway (Lee et al, 2018), and TNF signaling pathway (Pooladanda et al, 2019) from our prediction results have been reported to regulate inflammation by mediating the expression of iNOS.…”
Section: Discussionmentioning
confidence: 55%
“…As shown in Figure 4 , the HT extract significantly reduced the secretion of IL-6 and NO under the nontoxic dosages, which indicated that the HT formula would be a potential anti-inflammatory formula in accordance with the prediction results. Furthermore, our experimental results suggested that the HT extract could decrease the LPS-induced excessive expression of the iNOS ( Figure 5 ), which has been reported to promote the production of IL-6 and NO during the development of RA (Li et al, 2017; Liu et al, 2018). As well known, iNOS is the downstream signal in the network of inflammatory cascade reaction, and several signaling pathways including the Toll-like receptor signaling pathway (Li et al, 2019), PI3K–Akt signaling pathway (Cao et al, 2019), HIF-1 signaling pathway (Lee et al, 2018), and TNF signaling pathway (Pooladanda et al, 2019) from our prediction results have been reported to regulate inflammation by mediating the expression of iNOS.…”
Section: Discussionmentioning
confidence: 55%
“…A recent study characterized the inflammatory role of GATA1 in RASFs , and therefore we evaluated the expression of GATA1 in OPTN–down‐regulated RASFs. Overall, the expression of GATA1 was obviously higher after down‐regulating OPTN, but the difference compared to control RASFs was not significant (Figure F) due to the wide range of standard deviation among patients.…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that an increase in anti-inflammatory cytokines may have resulted from an immunomodulatory response to neuroinflammation. Although not in the CNS, there were several reports that GATA1 was involved in the expression of inflammatory mediators in the peripheral system ( Masuda et al, 2004 ; Nigo et al, 2006 ; El Gazzar, 2007 ; Cole et al, 2010 ; Liu et al, 2018 ; Abdul Qayum et al, 2019 ). These findings might support the notion that GATA1 is involved in the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%